Optimization of Early Detection Performance of Kamneg Unit in Overcoming Radical Groups in the Jurisdiction of Kendal Resort Police - Razan, Naufal (Advances in Police Science Research Journal, 2024)
Overcoming radical groups in Kendal Regency is carried out by the Kamneg Unit by doing early detection of the presence and activities of radical groups. Early detection that is requires appropriate action so that the information obtained can be kept well by the Kamneg Unit as comparative data for subsequent early detection activities and is useful for leaders and related functional units to determine the right policy towards the security and public order disturbances. According to the Kamneg Unit’s intelligence data, the data on radical groups is not up-to-date with current conditions. This research aims to describe the organisational resources owned by the Kamneg Unit and describe the performance of the Kamneg Unit’s early detection in overcoming radical groups. The research method used is a qualitative method with descriptive research and field research. Data were obtained from interviews with Kamneg Unit personnel, document analysis by reducing data related to early detection activities against radical groups, and observation through observation and recording of ongoing early detection activities. The results showed that the performance of early detection in overcoming radical groups based on Management theory and Perkabaintelkam Polri No. 1 of 2013 about Police Intelligence Investigations has been running, but not optimal because there are still various obstacles related to human resources, supporting infrastructure, mastery of investigation methods, and management of intelligence data related to radical groups which are influenced by internal and external factors. Forms of optimisation of the Kamneg Unit’s early detection performance in overcoming radical groups include: completing intelligence administration, recollecting data on radical groups in Kendal Regency, approaching religious leaders and community leaders in religious activities, and using the latest intelligence technology. The conclusions of the research are (1) the utilisation of organisational resources has not fully supported early detection activities against radical groups so that obstacles are found in its implementation and (2) early detection performance in overcoming radical groups is not optimal so that problem solving is needed for the competence of knowledge, skills, and attitudes of Kamneg Unit personnel.